2022
DOI: 10.3390/s22031252
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Software Architecture Evaluation for Industry: A Comprehensive Review

Abstract: Processes for evaluating software architecture (SA) help to investigate problems and potential risks in SA. It is derived from many studies that proposed a plethora of systematic SA evaluation methods, while industrial practitioners currently refrain from applying them since they are heavyweight. Nowadays, heterogeneous software architectures are organized based on the new infrastructure. Hardware and associated software allow different systems, such as embedded, sensor-based, modern AI, and cloud-based system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 93 publications
0
21
0
1
Order By: Relevance
“…The embedded tool in the SA evaluation framework supports the evaluation's activities toward the automation of analysis within a framework. The tool and technology inside HSAEF is an intrinsic part that fits the framework's functionalities, and structures [1]. This research suggests PM tools and techniques to ingrate with HSAEF.…”
Section: Previous Research Methods and Materialsmentioning
confidence: 90%
See 3 more Smart Citations
“…The embedded tool in the SA evaluation framework supports the evaluation's activities toward the automation of analysis within a framework. The tool and technology inside HSAEF is an intrinsic part that fits the framework's functionalities, and structures [1]. This research suggests PM tools and techniques to ingrate with HSAEF.…”
Section: Previous Research Methods and Materialsmentioning
confidence: 90%
“…In this research, PM is suggested to integrate and adapt to HSAEF as a technique for addressing the targeted quality attributes (security and performance) [33]; however, features and factors were identified by [1]. Despite this progress, the PM's applicability to software engineering has two problems.…”
Section: Granularitymentioning
confidence: 99%
See 2 more Smart Citations
“…Rekayasa kebutuhan perangkat lunak adalah model atau pendekatan sistematis yang secara signifikan dikembangkan para peneliti dalam dekade terakhir (Belfadel, Laval, Bonner Cherifi, & Moalla, 2022) (Franch, Henriksson, Ralyté, & Zdravkovic, 2121) (Redouane, 2021). Arsitektur perangkat lunak dapat dipandang sebagai sekumpulan sistem yang secara komprehensif mencakup interaksi komponen, lingkungan operasional, prinsip desain, fungsionalitas perangkat lunak, dan sering mencakup perspektif perangkat lunak evolusioner masa depan (Sahlabadi, Muniyandi, Shukur, & Qamar, 2022) (Yang, Jiang, Shang, & Norouzi, 2021) (Venters, 2018) (Hasselbring, 2018).…”
Section: Metode Penelitianunclassified